Botulism outbreaks in natural environments – an update - Espelund, Mari; Klaveness, Dag (Frontiers in Microbiology, 2014)
Clostridium botulinum comprises a diverse group of botulinum toxin-producing anaerobic rod-shaped spore-forming bacteria that are ubiquitously distributed in soils and aquatic sediments. Decomposition of plants, algae and animals creates anaerobic environments that facilitate growth of C. botulinum, which may then enter into food webs leading to intoxication of animals. Via saprophytic utilization of nutrients, the bacteria rapidly sporulate, creating a reservoir of highly robust spores. In the present review, we focus on the occurrence of C. botulinum in non-clinical environments, and examine factors influencing growth and environmental factors associated with botulism outbreaks. We also outline cases involving specific environments and their biota. In wetlands, it has been found that some C. botulinum strains can associate with toxin-unaffected organisms—including algae, plants, and invertebrates—in which the bacteria appear to germinate and stay in the vegetative form for longer periods of time. We suggest the need for future investigations to resolve issues related to the environments in which C. botulinum spores may accumulate and germinate, and where the vegetative forms may multiply.